Use of blockchain techonology in the field of highest education in Republic of Kazakhstan - Turginbayeva, A.N.; Tarabella, A.; Тanassoglo , Y. (BUKETOV BUSINESS REVIEW, 2018)
In this article the problem of acceptable application of blockchain technology is considered in conditions of Kazakhstan. In the main part the extensive theoretical review of foreign researches is made about entities of technology and such fields of its application as bank branch, medicine, health care, business processes. Experience of some countries is analyzed, where the virtual currencies recognized as the tool with the same payment functions, as well as the State currencies. There’s the statistics of growth of crypto currency cost and the number of transactions with it for the period of last 3 years. Korea, Germany, UK, UAE are highlighted as countries actively forming the market of blockchain industry. It is noted that the Kazakhstani experience hasn't defined legal status of crypto currency, at which electronic money isn't belonged neither to goods, nor to currencies, nor to stock market. Respectively, in the existing Tax Code of the country there are no norms of the taxation crypto currencies. Being allocated with results of a research, except a guarantee of transparency, security and confidentiality of blockchain technology, such potential directions and its application in the sphere of the higher education, as: confirmation of the actual qualification of students, ensuring authenticity of documents of students, direct access for the employer to documents university graduate, Open access for investors to project works of students, digitalization all procedures of educational process of higher education institution, universal system of cataloguing of scientific works of Professors of university.